A SnO2 shell for high environmental stability of Ag nanowires applied for thermal management. Issue 7 (20th January 2021) - Baranowska-Korczyc, Anna; Mackiewicz, Ewelina; Ranoszek-Soliwoda, Katarzyna; Nejman, Alicja; Trasobares, Susana; Grobelny, Jarosław; Cieślak, Małgorzata; Celichowski, Grzegorz
Abstract : The study presents a rapid method of SnO2 shell formation on AgNWs for both high environmental stability and thermal management on para -aramid fabric. Abstract : Since silver nanowires (AgNWs) show high infrared reflectance many studies present their applicability as thermal management products for various wearable textiles. However, their use for practical purposes is only partially evaluated, without focusing on improving their low atmospheric and liquid stability. This report describes a new approach for the topic and proposes a facile method of Ag nanowire passivation with a SnO2 layer for high environmental stability and retention of high infrared reflectance. The one-step passivation process of AgNWs was carried out in the presence of sodium stannate in an aqueous solution at 100 °C, and resulted in the formation of core/shell Ag/SnO2 nanowires. This study presents the morphological, chemical, and structural properties of Ag/SnO2 NWs formed with a 14 nm thick SnO2 shell, consisting of 7 nm rutile-type crystals, covering the silver metallic core. The optical properties of the AgNWs changed significantly after shell formation, and the longitudinal and transverse modes in the surface plasmon resonance spectrum were red shifted as a result of the surrounding media dielectric constant changes. The passivation process protected the AgNWs from decomposition in air for over 4 months, and from dissolution in a KCN solution at concentrations up to 0.1 wt%. Moreover, the report shows the microwave irradiation effect on the shell synthesis and previously synthesised Ag/SnO2 NWs. The post-synthesis irradiation, as well as the SnO2 shell obtained by microwave assistance, did not allow long-term stability to be achieved. The microwave-assisted synthesis process was also not fast enough to inhibit the formation of prismatic silver structures from the nanowires. The Ag/SnO2 NWs with a shell obtained by a simple hydrolysis process, apart from showing high infra-red reflectance on the para -aramid fabric, are highly environmentally stable. The presented SnO2 shell preparation method can protect the AgNW's surface from dissolution or decomposition and facilitate the designing of durable smart wearable thermal materials for various conditions.